2002
DOI: 10.1063/1.1435802
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a magic discrete family of ultrabright Si nanoparticles

Abstract: We demonstrate that electrochemically etched, hydrogen capped Si n H x clusters with n larger than 20 are obtained within a family of discrete sizes. These sizes are 1.0 (Si 29 ), 1.67 (Si 123 ), 2.15, 2.9, and 3.7 nm in diameter. We characterize the particles via direct electron imaging, excitation and emission optical spectroscopy, and colloidal crystallization. The band gaps and emission bands are measured. The smallest four are ultrabright blue, green, yellow and red luminescent particles. The availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
221
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(243 citation statements)
references
References 32 publications
18
221
0
4
Order By: Relevance
“…5 The silicon wafers were cleaved into 2.5 x 4.5 cm strips, and immersed in 50:1 solution of deionized water and hydrofluoric acid (49%, Fluka) for 3-4 minutes for native oxide removal. The silicon was then laterally anodized while being dipped into a 3:2:1 solution of hydrogen peroxide, H 2 O 2 , (30% by volume), methanol (≥ 98% purity), and HF (49%, Fluka).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The silicon wafers were cleaved into 2.5 x 4.5 cm strips, and immersed in 50:1 solution of deionized water and hydrofluoric acid (49%, Fluka) for 3-4 minutes for native oxide removal. The silicon was then laterally anodized while being dipped into a 3:2:1 solution of hydrogen peroxide, H 2 O 2 , (30% by volume), methanol (≥ 98% purity), and HF (49%, Fluka).…”
Section: Methodsmentioning
confidence: 99%
“…The nanoparticles were dispersed into an organic solvent by sonicating the strips for 15 minutes. Unlike Belomoin et al, 5 no post-processing steps were used to break down larger structures and recover larger crystals. We were very careful to perform all experiments in controlled atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] The size tunable emission [18][19][20] , high brightness 21 , and high photostability compared to organic dyes 22 , have made SiNPs attractive materials as fluorescent cellular markers. In addition, silicon is abundant and economical 23 but more importantly silicon has low inherent toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Belomoin et al [10] demonstrated that electrochemically etched, hydrogen-capped Si n H x clusters with n larger than 20 are obtained as a family of discrete sizes. These sizes are 1.0 (Si 29 ), 1.67 (Si 123 ), 2.15, 2.9, and 3.7 nm in diameter.…”
Section: Electrochemical Etching and Ultrasonicationmentioning
confidence: 99%